A comparative performance analysis on NEMO-QoS and MIPv6-QoS in heterogeneous environments - Noor, R.M.; Edwards, C. (2011)
Mobility management in heterogeneous networks is an important area since the mobile network may be moving between multiple types of access networks which involve several service providers such as 802.11b WLAN, 802.16 WiMAX and UMTS Networks. In crowded environments, the bottleneck is often between the access link and the mobile network. Being able to prioritize the traffic and allocate a minimum bandwidth guarantee for each user is crucial in this environment. This study presents a novel dynamic QoS provisioning mechanism for network mobility in heterogeneous networks integrated with IEEE 802.21 Media Independent Handover (MIH) protocol. Network Mobility (NEMO) Basic Support protocol has three important nodes Mobile Network Nodes (MNNs), Mobile Router (MR) and Home Agent (HA). The dynamic QoS provisioning mechanism which consists of traffic marking, prioritizing and scheduling are implemented at the mobile network node domain. While the admission control module is implemented at a mobile router domain. Several experiments are conducted to evaluate the mechanism. The results have shown the importance of less packet loss and delay and higher packet forwarding rate.